Analisis Praktek Manajemen SDM Perbankan Syariah Milik Pemerintah di Sumatera Barat - Kenedi, Jon (Jurnal Ekonomi, 2013)
This study purposed to describe, explain and know management practices in West Sumatra particularly Islamic Banking owned by the goverment. The study population comprised 4 Islamic Bank are goverment-owned: BRI Syariah, BNI Syariah, Bank Syariah Mandiri and Bank Syariah Nagari, using descriptive statistic as a tool of analysis. The result showed that Islamic Banking is mainly state-owned Islamic bak in West Sumatra has been implementing management practices but has not been fully impelmented optimally.